Interruptions and politeness in David Letterman show “my guest no need introduction” Shah Rukh Khan episode - Christiani Tiwi Sumanti; Barli Bram (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2021)
This paper analyzed interruptions and politeness in the David Letterman Show. The data were collected from the show “My Guest No Need Introduction.” The study was qualitative research, and the data were  analyzed and then classified into types of interruptions. Results showed 32 interruptions in the conversation uttered by two speakers in the show, more specifically 26 times of overlap interruptions, three times of simple interruptions, twice of silent interruptions, and once of butting-in interruption. It can be concluded that, first, the appropriate interruptions display positive strategies of politeness in the David Letterman Show. Interruptions could be done for a specific purpose to strengthen the bond between two speakers and to avoid misunderstanding.  Second, the interruptions show politeness in conversation. Politeness appears to clarify statements to prevent misunderstandings between cultures.DOI: 10.26905/enjourme.v6i1.5962